(untitled) (MAUSAM, 1988)
The spatial structure, of and distances between, rainfall-areas in southwestern Nigeria were analysed using the cross-correlation technique. Data were analysed for three weather situations, namely linesquall, monsoon and thunderstorm periods. The rainfall cross-correlation field was found for all the weather situations to be elliptical in shape with the major axis following the trend of the dominant relief in the region. However, typical distances were found to separate the rainfall areas according to the weather situation: 50 km apart in monsoon rains, 75 km apart in line-squall rains but 100 km apart in thunderstorms rains.